Pengaruh Digitalisasi dan Penyederhanaan Proses Layanan Terhadap Loyalitas Pelanggan yang Dimediasi Oleh Kepuasan Pelanggan di PT. Indosat Ooredoo Hutchison - Dally, Shanna Daniela; Bastaman, Aam (JURNAL ILMIAH EDUNOMIKA, 2025)
Telecommunication companies are faced with a major challenge to improve the efficiency and effectiveness of their services. PT. Indosat Ooredoo Hutchison, as one of the major players in the Indonesian telecommunications industry, recognizes the importance of digitizing and simplifying service processes to meet increasingly high customer expectations. This study aims to analyse the effect of digitizing customer service and simplifying service processes on customer satisfaction and loyalty. The research method uses quantitative research. The results of the study indicate that the application of digital technology in customer service can increase satisfaction by improving quality, accelerating and providing more consistent service. Satisfaction obtained from a good service experience is the main factor that encourages customers to remain loyal and interact longer with the company. Simplifying the service process more efficiently increases customer satisfaction and, as a result, increases customer loyalty. The service process simplified through technology facilitates faster and more efficient interactions, which contributes to increased customer loyalty. The conclusions drawn from the above explanation are, (1) Digitalization of customer service has a positive effect on customer satisfaction; (2) Simplifying the service process has a positive effect on customer satisfaction; (3) Customer satisfaction has a positive effect on customer loyalty; (4) Digitalization of customer service has a positive effect on customer loyalty; (5) Customer satisfaction mediates the effect of customer service digitalization on customer loyalty; (6) Customer satisfaction mediates the effect of service process simplification on customer loyalty; (7) The use of technology to simplify the service process strengthens customer loyalty.